2020
DOI: 10.1371/journal.pone.0229450
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of perioperative transfusions using an artificial neural network

Abstract: Background Accurate prediction of operative transfusions is essential for resource allocation and identifying patients at risk of postoperative adverse events. This research examines the efficacy of using artificial neural networks (ANNs) to predict transfusions for all inpatient operations. Methods Over 1.6 million surgical cases over a two year period from the NSQIP-PUF database are used. Data from 2014 (750937 records) are used for model development and data from 2015 (885502 records) are used for model val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Factually, there is a growing evidence of AI application in TM, largely machine learning (equipment) but also deep learning applications (donor mobilization, stock management, cross matching, transfusion prediction in surgical interventions and prescription). In the advanced world, machine learning has been introduced in the clinical decision-making for transfusion, using data sets and stochastic dynamic programming (30,31) to predict the need (32)(33)(34).…”
Section: Some Illustrative Factsmentioning
confidence: 99%
“…Factually, there is a growing evidence of AI application in TM, largely machine learning (equipment) but also deep learning applications (donor mobilization, stock management, cross matching, transfusion prediction in surgical interventions and prescription). In the advanced world, machine learning has been introduced in the clinical decision-making for transfusion, using data sets and stochastic dynamic programming (30,31) to predict the need (32)(33)(34).…”
Section: Some Illustrative Factsmentioning
confidence: 99%
“…As this study was aimed at RBC inventory management, the biological plausibility of key predictors was not directly addressed. Recent publications on the prediction of perioperative RBC transfusions 46,47 and the prediction of RBC transfusion for patients with acute gastrointestinal bleeding 48 using patient level data also showed that laboratory test results (e.g., INR, creatinine, RDW, etc.) were important predictors for RBC transfusions.…”
Section: Notementioning
confidence: 99%
“…Data without label are grouped based on similarity between the input data. The data are then classified after the dataset are labelled to train [25,26]. ANN is able to perform non-linear statistical modeling and can be an alternative to logistic regression [27].…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%